Production of antihydrogen atoms by 6 keV antiprotons through a positronium cloud - P. Adrich; P. Blumer; G. Caratsch; M. Chung; P. Cladé; P. Comini; P. Crivelli; O. Dalkarov; P. Debu; A. Douillet; D. Drapier; P. Froelich; et al. (European Physical Journal C: Particles and Fields)
Abstract We report on the first production of an antihydrogen beam by charge exchange of 6.1 keV antiprotons with a cloud of positronium in the GBAR experiment at CERN. The 100 keV antiproton beam delivered by the AD/ELENA facility was further decelerated with a pulsed drift tube. A 9 MeV electron beam from a linear accelerator produced a low energy positron beam. The positrons were accumulated in a set of two Penning–Malmberg traps. The positronium target cloud resulted from the conversion of the positrons extracted from the traps. The antiproton beam was steered onto this positronium cloud to produce the antiatoms. We observe an excess over background indicating antihydrogen production with a significance of 3–4 standard deviations.